Color me obsessed [videorecording (DVD)] : a film about the Replacements - Bechard, Gorman (MVD Visual, 2012)
Over The Replacements' 12-year existence, its live sets were magical. Gorman Bechard's remarkable history of the Mats takes us from their first show and everywhere in between. He relies solely on the fans; memories of their albums & antics.